Hubungan Antara Efikasi Diri Dengan Minat Membaca Pada Siswa SMK - Yaumil Akhir, Yan Rachmawati; , Dr. Lisnawati Ruhaena, M.Si., Psikolog (2017)
The success of students in the future is determined by reading. Reading activities are influenced by reading interest. Factors that may affect in reading interest is self efficacy because it has an important role in growing interest in that's activities. The purpose of the research is to know the relationship between self efficacy and interest in reading vocational high school students. The samples were 179 students with using Cluster Random Sampling technique sample. Data collection method uses quantitative research method with measuring instrument used in the study are self efficacy scale and reading interest scale. Data analysis technique used technique correlation product moment of Carl Pearson. The results showed that self efficacy has a correlation with reading interest of 0,394 the level significance 0,000, means that there is positive relationship highly significant between self efficacy with reading interest in vocational high school students. Keywords : reading interest, self efficacy, success, vocational high school students